Incidental Finding of Nocardia: A Case Series from a Tertiary Care Centre in Uttarakhand - Aroop Mohanty; Suneeta Meena; Subodh Pandey Kumar; Puneet Kumar Gupta; Neelam Kaistha; Pratima Gupta; Mithilesh Kumar Jha; Sasi Rekha (Case Reports in Infectious Diseases)
Nocardiosis is a rare bacterial infection that may lead to a severe disease. These infections are rare among normal population and are showing an increasing trend worldwide attributable to the increase in the immunosuppressed population. Most of these patients present with nonspecific clinical features such as fever, productive cough, and exertional dyspnoea as seen in our series of patients which makes it difficult to be diagnosed. Pulmonary nocardiosis is rarely clinically suspected and often diagnosed very late in the course of disease resulting in high mortality. A similar observation was made in one of our cases where the patient was being treated on the lines of pneumonia, and in the end she was diagnosed with pulmonary nocardiosis. In view of the limited literature available, we report here a case series of pulmonary nocardiosis in immunosuppressed patients diagnosed incidentally by fungal KOH mount. The most common conditions causing immunosuppression were type II DM, COPD, and pulmonary tuberculosis.